2018
DOI: 10.1371/journal.pone.0190806
|View full text |Cite
|
Sign up to set email alerts
|

Validation of the Spanish version of the Irrational Procrastination Scale (IPS)

Abstract: The present study is centered in adapting and validating a Spanish version of the Irrational Procrastination Scale (IPS). The sample consists of 365 adults aged 18–77 years (M = 37.70, SD = 12.64). Participants were administered two measures of procrastination, the IPS and the Decisional Procrastination Questionnaire, as well as the Big Five Inventory, and the Satisfaction With Life Scale. First, the factor and replication analysis revealed that the internal structure of the scale is clearly one-dimensional, s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
24
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(33 citation statements)
references
References 29 publications
7
24
1
Order By: Relevance
“…As presented in Table 1 , the point-measure correlations ( r pm ; comparable with item-total correlations in CTT) of the nine items on the scale range from 0.58 to 0.74, indicating the absence of non-modeled dependence among the items and potentially a common underlying construct of all items ( Linacre, 2011 ). In accordance with previous studies ( Prayitno et al, 2013 ; Rozental et al, 2014 ; Svartdal and Steel, 2017 ; Guilera et al, 2018 ), the reversed items (Items 2, 6, 9) showed the lowest point-measure correlations, possibly reflecting a statistical artifact in reverse scoring ( Schmitt and Stuits, 1985 ). Moreover, the values for the standard error ( SE ) in Table 1 range from 0.09 to 0.10 only, demonstrating a high level of measurement precision.…”
Section: Resultssupporting
confidence: 91%
See 1 more Smart Citation
“…As presented in Table 1 , the point-measure correlations ( r pm ; comparable with item-total correlations in CTT) of the nine items on the scale range from 0.58 to 0.74, indicating the absence of non-modeled dependence among the items and potentially a common underlying construct of all items ( Linacre, 2011 ). In accordance with previous studies ( Prayitno et al, 2013 ; Rozental et al, 2014 ; Svartdal and Steel, 2017 ; Guilera et al, 2018 ), the reversed items (Items 2, 6, 9) showed the lowest point-measure correlations, possibly reflecting a statistical artifact in reverse scoring ( Schmitt and Stuits, 1985 ). Moreover, the values for the standard error ( SE ) in Table 1 range from 0.09 to 0.10 only, demonstrating a high level of measurement precision.…”
Section: Resultssupporting
confidence: 91%
“…Empirical evidence from past work has largely pointed to the unidimensionality of the IPS (e.g., Svartdal et al, 2016 ; Svartdal, 2017 ; Kim et al, 2020 ) – although two studies ( Prayitno et al, 2013 ; Rozental et al, 2014 ) found the reversely scored items to load on a different factor compared to the rest of the items on the scale, these authors concluded that this could just be a reflection of a methodological artifact ( Schmitt and Stuits, 1985 ). There is also converging evidence from several studies demonstrating the psychometric soundness of the IPS regarding internal consistency and relations to other instruments ( Rebetez et al, 2014 ; Rozental et al, 2014 ; Svartdal and Steel, 2017 ; Guilera et al, 2018 ).…”
Section: Introductionmentioning
confidence: 92%
“…We will assess: (1) self-efficacy 57 ; (2) activation 58 ; (3) sense of coherence 59 ; (4) health literacy 60 and (5) procrastination. 61 …”
Section: Methods and Analysismentioning
confidence: 99%
“…(3) sense of coherence 59 ; (4) health literacy 60 and (5) procrastination. 61 Self-efficacy Self-efficacy will be measured using the Self-Efficacy Scale. 57 To measure General Self-Efficacy Subscale (17 items including individuals' beliefs in their ability to perform well in a variety of situations) and Social Self-Efficacy Subscale (six items).…”
Section: Secondary Outcomesmentioning
confidence: 99%
See 1 more Smart Citation